1984
DOI: 10.1136/bmj.288.6423.1032
|View full text |Cite
|
Sign up to set email alerts
|

Fasting plasma magnesium concentrations and glucose disposal in diabetes.

Abstract: Fasting plasma concentrations of magnesium were measured by neutron activation analysis in 30 nondiabetics and 87 diabetics (55 non-insulin-treated, 32 insulin treated). Plasma concentrations of magnesium were lowest in the insulin treated group (mean 0 84 (SEM 0 01) mmol/l; 2 0 (0 02) mg/100 ml), intermediate in the non-diabetics (mean 0 89 (SEM 0 01) mmol/l; 2 2 (0-02) mg/100 ml), and highest in the non-insulintreated diabetics (mean 0-95 (SEM 0 02) mmol/l; 2 3 (005) mg/100 ml). In all diabetics plasma magne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
63
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(74 citation statements)
references
References 14 publications
(6 reference statements)
10
63
1
Order By: Relevance
“…19 Serum levels of magnesium have been found by several investigators to correlate inversely with fasting blood glucose concentration, post prandial blood glucose and the percentage of HbA1C. 8,20,[22][23][24][25] The present study also revealed that patients with low serum magnesium levels had poor glycemic control. There was statistically significant association between low serum magnesium levels and higher FBS, PPBS and HbA1C%.…”
Section: Discussionsupporting
confidence: 55%
“…19 Serum levels of magnesium have been found by several investigators to correlate inversely with fasting blood glucose concentration, post prandial blood glucose and the percentage of HbA1C. 8,20,[22][23][24][25] The present study also revealed that patients with low serum magnesium levels had poor glycemic control. There was statistically significant association between low serum magnesium levels and higher FBS, PPBS and HbA1C%.…”
Section: Discussionsupporting
confidence: 55%
“…In effect, hypermagnesemia inhibits insulin secretion (Zofkova et al, 1988), while it enhances insulin sensitivity through increase in binding affinity of insulin to its receptors (Yajnlk et al, 1984;Paolisso et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…A complex interplay exists between magnesium and glucose metabolisms. It plays an important role in the activities of various enzymes which are involved in glucose oxidation, and it may play a role in the release of insulin [17][18][19]. It is mainly intracellular and its uptake is stimulated by insulin [19,20].…”
Section: Discussionmentioning
confidence: 99%